Transmission Error Analysis of the 2K-V Reducer based on Rigid-flexible Coupling - Zhou Zhengdao; Jia Haili (Jixie chuandong)
Taking the high-precision 2 K-V20 reducer for industrial robots as the research object,by using the technology of multi-flexible-body dynamics,the rigid-flexible coupling model of the reducer is established in Recur Dyn. The motion characteristics of each part are analyzed through virtual prototype simulation,and the result is approximately with the theoretical value,which testifies the correctness of the model.Based on this rigid-flexible coupling model,some models with different error sources are established,and their effects on the reducer transmission error are analyzed through simulation. The conclusion could provide some reference value for the designing and manufacturing of the 2 K-V reducer.